Magyarországi orvostanhallgatók Bázelben készült disszertációinak szerepe a hazai orvostársadalom ismereteinek alakításában a 18. században - Hegyi, Ádám (Gerundium, 2015)
THE ROLE OF THE DISSERTATIONS OF HUNGARIAN MEDICAL STUDENTS IN BASEL IN THE KNOWLEDGE DEVELOPMENT OF HUNGARIAN MEDICAL COMMUNITIES IN THE 18TH CENTURY. Medical professionals acquired new knowledge for the medical practice not from scientiic journals, as today, but from books, academic thesis, disputes, dissertations received through the correspondence with Western-European professors and the mediation of students studying abroad. he university in Basel was popular among modern Hungarian protestants, but only some studied medicine, and only 5 people wrote a medical dissertation. Presumably students distributed these works amongs themselves, and they were not particularly used in the every day work of medical practicioners. hese dissertations were included in few Hungarian collections (Debrecen, Sárospatak) opposed to more popular theological works.